TANGGUNG JAWAB NEGARA DALAM EKONOMI ISLAM (Pemikiran Muhammad Al-Baqir As-Sadr) - Sri Wigati (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2015)
This paper of the discussion focuses on the Islamic economics thought of Muhammad al-Baqir al-Sadr, his biography, and his educational background particularly in relation to the concept of Islamic economy. Al-Sadr refuses all kinds of conventional economic theory and suggests that the economic theories are supposed to be explored newly from al-Qur'an and al-hadith. In order not to be bias, this paper is going to focus on al-Sadr’s idea about the responsibility of the state. According to him, the responsibility of the state is divided into three, namely social security, social balance and intervention. These three responsibilities are certainly on the hand of the government to regulate and direct the life of the people. In this case, the head of state is the one who has to guarantee for the balance of social and security welfare of his people. He might also intervene in order to control and regulate the economic condition of the state.